2020
DOI: 10.1002/fsn3.1651
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Fe3O4@NH2 in soil and their fixation effect to reduce lead translocation in two rice cultivars

Abstract: The fate of nanoparticles in the ecological chain of agriculture has been concerned as their potential pollution and biological effect to humans with rapid development and massive emission of nanomaterials. Here, we found that two rice cultivars ( Oryza sativa L ) have different heavy metal accumulation results in the roots and shoots after 15 days growth. Two rice cultivars ( Oryza sativa L ), grown in soil containing magnetite (Fe 3 O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Even in drought-like conditions, Ahmed et al discovered that co-treating rice with hydrogel nanoparticles and iron oxide nanoparticles prepared from Bacillus strain RNT1 was able to reduce the reactive oxygen content and Cd adsorption by rice [ 34 ]. Fe 3 O 4 @NH 2 nanoparticles can be used to immobilize the heavy metal Pb in soil and inhibit Pb uptake by rice roots and shoots [ 35 ], and the nanoparticles can be recycled. In 2018, Huang et al found that Fe 3 O 4 NPs and zero-valent iron nanoparticles were better at preventing arsenic migration to the above-ground parts of rice seedlings compared to high-quality graphene oxide, multilayer graphene oxide, 20 nm hydroxyapatite (HA 20 ), and 40 nm hydroxyapatite (HA 40 ) [ 36 ].…”
Section: Effect Of Monps On the Growth Of Ricementioning
confidence: 99%
“…Even in drought-like conditions, Ahmed et al discovered that co-treating rice with hydrogel nanoparticles and iron oxide nanoparticles prepared from Bacillus strain RNT1 was able to reduce the reactive oxygen content and Cd adsorption by rice [ 34 ]. Fe 3 O 4 @NH 2 nanoparticles can be used to immobilize the heavy metal Pb in soil and inhibit Pb uptake by rice roots and shoots [ 35 ], and the nanoparticles can be recycled. In 2018, Huang et al found that Fe 3 O 4 NPs and zero-valent iron nanoparticles were better at preventing arsenic migration to the above-ground parts of rice seedlings compared to high-quality graphene oxide, multilayer graphene oxide, 20 nm hydroxyapatite (HA 20 ), and 40 nm hydroxyapatite (HA 40 ) [ 36 ].…”
Section: Effect Of Monps On the Growth Of Ricementioning
confidence: 99%
“…Micro- and nanomaterials with different physical and chemical properties have been developed for human needs [ 1 , 2 ]. However, micro- and nanomaterials also show unexpected toxicity [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The environmental concentration of iron-based materials has been increased in the biota, including soil, air, and water [10]. Literature have reported the fate, biotransformation, bioaccumulation, and toxicity of such elements in various ecosystems [11,12]. In particular, aquatic environments are the most important destinations for iron-based compounds through wastewater drainage and land lls in populated areas.…”
Section: Introductionmentioning
confidence: 99%